Ultrasonographic evaluation of inflammatory swellings of buccal space - Srinivas K; Sumanth K; Chopra S (Wolters Kluwer Medknow Publications, 2009)
Objectives : The main objective of the study was a) to differentiate cellulitis and abscess in buccal space region, b) to study the ultrasonographic anatomy of cheek region and c) to investigate the use of ultrasound in the diagnosis of inflammatory swellings of cheek region. Patients and Methods : The study consisted of 25 patients with unilateral buccal space inflammatory swellings of odontogenic origin. The contra lateral side was used as control. Toshiba ultrasonographic device with a linear array transducer (5-8 MHz) was used. The areas of interest were scanned under both transverse and longitudinal sections and were interpreted by a single observer. The clinical diagnosis of cellulitis or abscess was confirmed by the absence or presence of pus respectively both sonographically and by aspiration. Also various anatomical structures present in buccal space were studied. Results : Clinically 23(92%) were diagnosed as buccal space abscess and 2 (8%) were cellulitis. Ultrasonographically and therapeutically 24 (96%) were buccal space abscess and 1 (4%) was cellulits. The sensitivity of clinical criteria over ultrasonographic diagnosis was 96% with a specificity of 100%. Also the cheek thickness in males and females varied from 8.2 to 17.1mm with a mean of 11.6mm±2.1 (SD) and 8.2 mm to 14.2 mm with a mean of 11±1.8 (SD). The subcutaneous tissue appeared moderately echogenic, buccinator - highly echogenic, deep adipose tissue - less echogenic and parotid duct was appreciated as a thin hyperechogenic band crossing the buccinator muscle. Buccal space, masticator space and parotid space were appreciated. Conclusion : This study supports the ultrasonographic method of imaging of orofacial inflammatory swellings with high sensitivity and specificity. This imaging modality can also help in aspiration of pus in different spaces. We have described the ultrasonographic anatomy of the above mentioned spaces which can help a beginner in this field.